Modelagem hidrológica no semiárido brasileiro: uso intenso da água, intermitência e mudanças climáticas - Lima, Thales Bruno Rodrigues (2025)
The complexity of hydrological processes, the scarcity and discontinuity of observed data and the emergence of uncertainties about the impact of climate change on water availability are factors that make hydrological modelling an essential tool for managing water resources, particularly in drylands. This study used the physically-based Model of Water Availability in Semiarid Environment (WASA) to assess: (i) the impact of intense use of water from small reservoirs associated with the hydrological dynamics of strategic reservoirs in the Jaguaribe Basin (75,000 km²); (ii) the capacity of the WASA model itself to simultaneously reproduce discharge (reservoir inflow) and intermittency in the Umbuzeiro River Basin (≈1000 km²); and (iii) the impact of climate change on discharge, intermittency and water availability at this latter scale. The results show that the intense use of water from small reservoirs causes a reduction of less than 10 per cent in the volume stored in the strategic reservoirs of the Jaguaribe River Basin (75 000 km²). The WASA model does not satisfactorily reproduce the generation of runoff and the intermittency pattern simultaneously on a daily scale, but on a monthly scale the model reproduces the processes satisfactorily (RMSE less than 50% of the mean value). Projections of average rainfall by the end of this century, under climate change scenarios RCP 4.5 (+10%) and 8. 5 (-14%), predicted by the Eta regional model (nested with the BESM, CanESM2, HadGEM2-ES and MIROC5 global climate models), indicate that water availability could vary from -73% to +43% (2025 - 2099), while the number of months with run-off could be reduced by up to 85% in the long term (2071 - 2099) compared to what was observed between 2004 and 2024.